The Prevalence of Phenylketonuria and other metabolic diseases in sick Iraqi children; the importance of the newborn screening program. - Thijeel, Rabab F. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Phenylketonuria (PKU) is one of the most important metabolic causes for mental retardation in children, in which early diagnosis would successfully prevent mental retardation, yet, there are some other serious metabolic diseases that share the same mode of presentation and some of the phenotypic manifestations also. Methods: During the period from August 2009 to August 2011, 63 cases were referred to the Children Welfare Teaching Hospital (CWTH) with clinical features of PKU, all were enrolled in this study, few blood drops on a special filter paper were taken from each patient and sent to a specialized metabolic laboratory in Saint Joseph University , using tandem mass spectrophotometry (MS/MS). The results were received through internet after being analyzed and interpreted.Aim: This study aimed to assess the prevalence of PKU and other inborn errors of metabolism among sick children, presenting with clinical features suggestive of PKU, what are the diseases that share same clinical presentation of PKU, and make a proper early diagnosis and management when possible. Results: out of the 63 cases, only 28(44.4%) came positive with different diseases, only 7(11.1%) were cases of PKU. The results also showed some other Inborn Errors of Metaboilsm(IEM): homocystinuria(HCY)or methionine adenosyltransferase(MAT) 7(11.1%),Methylmalonic academia (MMA)4(6.3%), maple serum urine disease (MSUD) in 3 cases(4.7%).The consanguinity was positive in 41 cases (65%). Positive family history was documented in 23(36.5%).All PKU cases had the background of consanguineous marriages (100%). Conclusions: PKU is one of the most important metabolic cause for mental retardation in our study, but some other serious metabolic defects like homocystinuria(HCY) or MAT, organic acidemias, maple syrup urine disease(MSUD) also causes mental retardation and share some of the phenotypic manifestations of PKU. Many families had positive history of affected siblings,especially those with consanguineous marriages.